Reconstrucción osteobiográfica en odontología forense - Suárez Ponce, Daniel Guillermo (2014)
In forensic science estimating osteo biographical reconstruction of a subject is an important part of the complex process of human identification. Osteo biographical reconstruction takes into account the methods for estimating age, sex, ancestry and stature based mainly on the study of craniofacial skull, morphology, metric dimensions, which support forensic science with an important battery data contributing to the identification of missing persons. In this sense, the dental chart which is regularly applied in identification is a fraction of all the information we can get the dental system. Here we can say, as for the bones, the cranium and teeth speak and tell the story of the missing person that was part of a living environment, a particular social group and an individuality that makes unique.